S2 The impact of continuous positive airway pressure (CPAP) therapy on cognitive function in older people with sleep disordered breathing (SDB) and co morbidity. (14th November 2013) - McMillan, A; Paniccia, L; Glasser, M; Edison, P; Simonds, AK; Morrell, MJ
Abstract : The impact of SDB on cognitive function is debatable, with sleepiness and intermittent hypoxia being implicated as potential mechanisms. The purpose of this study was to investigate the relationship between cognitive function and brain structure in older patients with SDB, who may be more vulnerable to cognitive decline, and in whom SDB is more common. A randomised controlled trial was carried out to determine if CPAP therapy could reverse any changes in cognitive function and brain structure. Methods: Older patients ≥65 years, with SDB [≥4% Oxygenation Desaturation Index (ODI) >7.5 events/hour] were randomised to CPAP therapy or Best Supportive Care (BSC) for 6 months. Cognitive function was assessed at baseline and after 6 months, using a battery of 8 cognitive tests designed to examine attention, executive function and memory. MR brain scans were also completed however analysis is on-going. Results: The CPAP (n = 17) and BSC (n = 17) groups were well matched for age [mean (SD)] 70.8(4.1) vs. 70.8(3.3) years; BMI: 30.1(6.0) vs. 31.4(3.8) Kg/m 2 ; Epworth sleepiness score (ESS): 9.4(4.3) vs. 9.4(4.8) and number of additional co morbidities/patient 2(1) vs. 2(1). ODI was higher in the CPAP group [35(22) vs. 19(15) events/hour p = 0.01]. Baseline cognitive function was similar between groups for all tests. At 6 months the CPAP group had improvements in both of the attention and executive function compared to the BSC group [Trail Making B: 94(56) vs. 83(45) seconds, p = 0.047; STROOP: 33(10) vs. 29(11) correct responses p = 0.03]. Other measures of cognitive function were not statistically improved following 6 months of CPAP therapy. Subjective sleepiness did not improve significantly between groups [Change in ESS: CPAP -2.1(0.8) vs. BSC -0.7(0.7) p = 0.261]; however the ODI was significantly reduced with CPAP: 20(18.3) vs. BSC 3(10.7) events/hour p < 0.01. The mean (SD) daily CPAP usage was: 3.4(2.2) hours. Conclusion: 6 months of CPAP therapy improved the ODI, attention and executive function but not subjective sleepiness or memory in this small group of older patients with SDB. We speculate the improvements in attention and executive function were due to a reduction in intermittent hypoxia. This may be reflected in changes in brain structure.